A Comparative Analysis of the Formation of Civic Identity Practice in Foreign Countries (Халықаралық қатынастар және халықаралық құқық сериясы, 2024)
Nowadays, in the age of a fast-moving world and globalization maintaining and strengthening of the civic identity of society remains one of topical issues for both developing and developed countries. The question of what should be civic identity and what it should include is multifaceted and at the same time complex. Civiс identity is often seen in the context of an active citizen’s activities. If the problem is approached from the competencies of an active citizen point of view, then civic identity is formed on the knowledge, skills and attitudes possessed by a person. Active citizenship can also reveal the essence of civic identity. Understanding of it largely depends on the components of civic identity, which are formed depending on the ongoing government policy in this state.A comparative historical analysis of the process of civiс identity formation in foreign countries was carried out and a parallel was drawn between eastern and western states in order to identify the specifics of civiс identity. Particular attention has been paid to the peculiarities of the formation of civiс identity in national democratic states.In the result of the study, the article reveals that the formation of civiс identity of citizens in one state is not a model for other states. While some states only need to honor cultural traditions and mentality, some states need to increase the civiс activity of citizens, promote trust in the state, and pursue common interests. This shows that the process of formation of civiс identity in one country cannot serve as an example for another. The state should take into account its internal political, economic, social, and demographic characteristics when forming the civiс identity of its people.Key words: civiс identity, nation states, civiс society, civiс position, active citizen.